Memoria y olvido en imaginarios y paisajes urbanos - Alvarez-Calderón Silva-Santisteban , Rosabella (2025)
This essay explores how memory/remembering and oblivion/forgetting shape urban landscapes and collective imaginaries. Throughout history, societies have been molded by oral, written, and artistic traditions, as well as by spatial experiences and perceptions that foster attachments to place. In a continuous feedback process, the presence and absence of memory transform the built environment. Drawing on a comparative perspective between global contexts and two case studies in Lima, an international exposition known as La Feria del Hogar and the La Herradura seaside resort, we examine how memory, or its absence, influences city-making and the ways we imagine urban spaces.